Public Private Partnership in The Development of Road Infrastructure in Lampung Province - Utama, Realita; Yulianto, Yulianto; Hermawan, Dedy; Meutia, Intan Fitri (Journal of Research in Social Science and Humanities, 2025)
This study aims to examine the implementation of the Public Private Partnership scheme in road infrastructure development in Lampung Province, specifically through the BERKIBAR (Together We Fix Damaged Roads) Program. The main focus is directed at analyzing the effectiveness of partnership governance involving the public and private sectors based on the principles of good governance, active stakeholder participation, ethical standards of implementation, and indicator-based performance measurement. This study uses a qualitative approach with a case study design. Data collection techniques include in-depth interviews, direct observation, and document analysis. The results show that the BERKIBAR program has made a positive contribution in accelerating road infrastructure development, but still faces various structural and administrative obstacles. Weaknesses are seen in delays in physical project progress, minimal community involvement, and discrepancies between reporting and field realization. In addition, the indicator-based evaluation system has not been implemented comprehensively and systematically. Practically, these findings demonstrate the importance of strengthening collaborative governance in Public Private Partnerships to improve the efficiency and accountability of infrastructure development. The academic contribution of this study lies in the development of a sustainable partnership model based on the principles of New Public Governance as a relevant approach in the context of regional development.